MADDENİN HALLERİ KONUSUNUN EĞİTSEL OYUNLARLA ÖĞRETİMİ. - DEMİRCİOĞLU, Hülya; AKDEMİR, Medine Sultan (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2019)
Learning environments should no longer be the places where information is stored by heart. The learning environments should be transformed into the places where students learn the knowledge and skills that need for their lives in a natural process. Educational games are one of the techniques that will contribute to the development of such learning environments and the mental development of students. The aim of this study is to determine the effect of teaching supported by educational games on ninth grade students' achievement in the state of matter. In this study, quasi-experimental design was used. The research sample consists of a total of 42 students in the 9th grade. A "Topic of States of Matter Achievement Test" and unstructured observation were used to collect the data. The application period lasted for 4 weeks in both groups, except for pre- and post-tests. The data obtained from the test were analyzed statistically. As a result of the data obtained, it was determined that there was a significant difference in favor of the experimental group in terms of average scores of students' academic achievement. According to this result, it can be said that teaching based on educational games is more effective in increasing academic achievement than traditional teaching method.